Optimalisasi Strategi Guru Pendidikan Agama Islam Dalam Pembinaan Akhlakul Karimah Siswa Sekolah Dasar Masa Pandemik Covid-19 - Ranah (CV ODIS, 2021)
This study aims to describe (1) the moral development program. (2) the approach and steps developed by Islamic Religious Education teachers in fostering the morality of students. (3) factors supporting and inhibiting the moral development of students at SDN 9 Kampung Baru Simpang Empat Tanah Bumbu. The method used descriptive qualitative approach. The data analysis technique used by Miles and Huberman used by triangulation test. The results of the study show, (1) The program for the development of morality includes: Relationship to Allah by getting used to obeying worship, both sunnah and obligatory. Relationships with others are accustomed to behaving politely, politely, respecting and appreciating others. Relationship with the environment with love for the environment. The relationship with oneself maintains, takes care of the body and obeys the rules. (2) The approach and steps developed by Islamic Religious Education teachers in fostering the morality of students include: personal approach, example, habituation, punishment. (3) Supporting and inhibiting factors for fostering student morality, supporting factors are: the existence of self-awareness in students, role models in teachers, learning methods, cooperation and support from parents, facilities and infrastructure. While the inhibiting factors are lack of PAI subject hours, misuse of cellphones, student environment, unsupportive study background, limited supervision by the school.